Economic effect of corona pandemic on Saudi pro league football tournament (Applied in Saudi Pro League - AlThobaiti, Yousef (Jurnal MensSana, 2021)
The study aims to identify economic effects of Corona pandemic on Saudi football represented in SPL sector, and precautionary measures to reduce these effects on Saudi football. the researcher used the descriptive approach (survey studies), and the study sample was (75) academics specialists in sports administration and experts in the field of sports economics, and officials in the different sectors of SPL. There are negative effects of the Corona pandemic on the Saudi football sector, but also it has a positive impact that is to try to activate online management and virtual training, while the negative economic effects on players, administrators, clubs and the professional league’s revenues increase as the time of the pandemic continues. The Saudi footballer should have a plan to work online in case of natural disasters, and put a term in the contracts in the sports field In case of natural disasters that lead to the cancellation of a sporting event before its establishment, its postponement or non-completion, the method of termination of the contract shall be determined according to each case, with the activation of the role of online training in the association and sports clubs, and the activation of the role of electronic services.